On statistical reconstruction of vector random fields - Niedźwiecki, Maciej (Zielona Góra: Uniwersytet Zielonogórski)
The problem of statistical reconstruction of missing samples arbitrarily located within the rectangular segment of a Gaussian vector random field is considered. It is shown that the reconstruction is made up of the deterministic (predictable and hence unique) component and the stochastic (unpredictable and hence nonunique) component.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka